2014
DOI: 10.1021/jo5009146
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Chemosensors for Anions and Contact Ion Pairs with a Cavity-Based Selectivity

Abstract: The association of a concave macrocyclic compound to one or multiple fluorophores is an appealing strategy for the design of chemosensors. Indeed, as with biological systems, a cavity-based selectivity can be expected with such fluorescent receptors. Examples of calix[6]arene-based systems using this strategy are rare in the literature, and to our knowledge, no examples of fluorescent receptors that can bind organic contact ion pairs have been reported. This report describes the straightforward synthesis of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 72 publications
1
29
0
Order By: Relevance
“…Langton et al 32 demonstrated the utility of halogen bonding and its potential superiority to hydrogen bonding in achieving anion binding in water in a series of cyclodextrin-functionalized acyclic (57)(58)(59) and rotaxane (60-62) hosts ( Figure 20). Rotaxane 60, which bound anions via a combination of halogen bonding and hydrogen bonding, displayed a remarkably high affinity of 2,200 M À1 for I À and a selectivity of I À > Br À > Cl À > SO 4 2À in D 2 O.…”
Section: Halogen and Chalcogen Bondingmentioning
confidence: 99%
“…Langton et al 32 demonstrated the utility of halogen bonding and its potential superiority to hydrogen bonding in achieving anion binding in water in a series of cyclodextrin-functionalized acyclic (57)(58)(59) and rotaxane (60-62) hosts ( Figure 20). Rotaxane 60, which bound anions via a combination of halogen bonding and hydrogen bonding, displayed a remarkably high affinity of 2,200 M À1 for I À and a selectivity of I À > Br À > Cl À > SO 4 2À in D 2 O.…”
Section: Halogen and Chalcogen Bondingmentioning
confidence: 99%
“…tBuNH 3 + is more sterically hindered than PrNH 3 + and cannot be complexed by the calixarene cavity (Supporting Information, Figure S16). [39] While for receptor 7,w hich is devoid of ac avity,t he half-life of 98 si ss imilar to that observed for Cl À /NO 3 À antiport, alonger half-life of 71 swas observed in the case of calixarene 4. These results confirm the advantage of the calix [6]arene cavity for the transport of PrNH 3 Cl.…”
Section: Zuschriftenmentioning
confidence: 70%
“…This behavior is in agreement with previous research on the binding process of organic ion pairs with calix [6]arenes in organic solvents. [26,39] To confirm that PrNH 3 Cl does indeed enter the vesicles, both 1 Hand 35 Cl NMR experiments were undertaken with the aim of characterizing the interior of the vesicles,b efore and after transport. Paramagnetic species were used to distinguish between extra-and intravesicular species.Co 2+ ,aknown shift reagent for Cl À in the context of transmembrane transport, [34,35] was used for the 35 Cl NMR experiments and thulium(III)-1,4,7,10-tetraazacyclododecane-1,4,7,10-tetrakis(methylene phosphonate) (TmDOTP 5À ) [36] was used for the 1 HNMR experiments.F igure 3a shows the 1 HNMR spectra with and without calixarene 4 preincorporated in the lipid bilayer of the vesicles,r ecorded immediately after addition of 100 mm PrNH 3 Cl.…”
Section: Zuschriftenmentioning
confidence: 99%